Development of civic energy in rural areas in Poland - Marzec, Tomasz (Przegląd Prawa Rolnego, 2023)
The aim of this study is to answer the question of whether the legislator has provided sufficient support for organisational and legal forms of civic energy operating in rural areas. The implementation of this objective requires determining the legal framework for civic energy in EU and national law. The considerations carried out have led to the conclusion that the current regulation does not sufficiently support the development of civic energy initiatives. No regulations have yet been adopted to effectively encourage agricultural communities to implement RES projects or to provide the necessary financial support for this type of investment. Moreover, the national legislation on organisational and legal forms of civic energy continues to be inconsistent with EU law. Concluding, an attractive system of incentives, including financial incentives, should be developed while the economic risk of social investment in RES should be minimised.